Changes in Maternal Depression and Children's Behavior Problems: Investigating the Role of COVID-19-Related Stressors, Hair Cortisol, and Dehydroepiandrosterone. (November 2022) - Doan, Stacey N.; Ding, Madeleine; Burniston, Anna Beth; Smiley, Patricia A.; Chow, Chong Man; Liu, Cindy H.
Few studies have used longitudinal approaches to consider the cumulative impact of COVID-19-related stressors (CRSs) on the psychological adjustment of mothers and children. In the current study, we tracked changes in maternal depressive symptoms and children's behavioral problems from approximately 2 years before the pandemic (T1) to May through August 2020 (T2). Second, we explored maternal hair cortisol and dehydroepiandrosterone as predictors of change in maternal depressive symptoms. Mothers ( N = 120) reported on maternal and child psychological adjustment at both time points. Hair hormone data were collected in the lab at T1. Results suggest increases in children's internalizing symptoms from T1 to T2 and that higher levels of CRSs were associated with increased maternal depressive symptoms. Maternal and child adjustment were correlated. Maternal hair cortisol, but not dehydroepiandrosterone, was associated with significant increases in depressive symptoms. Findings underscore the importance of considering the family system and cumulative risk exposure on maternal and child mental health.